Pengaruh Model Pembelajaran Case Based Learning terhadap Keterampilan Proses Sains Siswa pada Materi Ekosistem di SMAN 4 Sigi - Minarni Minarni; I Nengah Kundera; Lilies Tangge; Sutrisnawati Sutrisnawati; Ahmad Ramadhan (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The purpose of this study was to describe the effect of Case Based Learning model on students' science process skills in ecosystem learning at SMAN 4 Sigi. This research is quantitative research using experimental methods. The population in this study were all students in the class. The research sample consisted of 50 students consisting of one experimental group and one control group. Data The data collection technique used student science process skills test instruments. The results showed that the significance value in the experimental class was 65.33, while in the control class it was 56.33 with a difference between the two of 9, including in the high category. Therefore, it can be concluded that: the case-based learning model affects students' science process skills on ecosystem material at SMAN 4 Sigi. These findings have several important implications for learning practices and education policy. Where, the implementation of CBL model is proven to be effective in improving students' science process skills. This shows that the case-based learning approach can facilitate a deeper and more applicable understanding of science concepts and encourage students to think critically and analytically. This approach allows students to be more actively involved in the learning process, increasing their participation and providing opportunities to apply their knowledge in relevant real-life situations. In addition, the findings also suggest that case-based teaching can be an effective tool in preparing students for future challenges. Thus, the integration of CBL models in the science learning curriculum can help students develop these skills early on.